If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1 = 3w + -7 Reorder the terms: -1 = -7 + 3w Solving -1 = -7 + 3w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-3w' to each side of the equation. -1 + -3w = -7 + 3w + -3w Combine like terms: 3w + -3w = 0 -1 + -3w = -7 + 0 -1 + -3w = -7 Add '1' to each side of the equation. -1 + 1 + -3w = -7 + 1 Combine like terms: -1 + 1 = 0 0 + -3w = -7 + 1 -3w = -7 + 1 Combine like terms: -7 + 1 = -6 -3w = -6 Divide each side by '-3'. w = 2 Simplifying w = 2
| 227-4x=32x+19 | | 13-7x=213-42x | | 2(3n+3)=-10 | | -9=3x+9 | | 13*21= | | 6y^2-19y+15=0 | | 85-6x=10-7x | | x^3-x^2-10=0 | | 96-3x=5x+8 | | X+4=3x-6 | | (12-4x)+(5-7x)=23 | | x^3+3*x+2=0 | | y=28-3(6) | | y=28-3(5) | | y=28-3(3) | | y=28-3(2) | | 20=40-4f | | 3(k+4)=12k-6 | | 6X+20=14x-68 | | x-6y=3v | | 76-7x=29x+16 | | 2x=8+2 | | 8(x+1)=2(x-2) | | 94-2x=25x+19 | | 8x-4=58 | | 7z-2=3z+6 | | 10-8x=82-29x | | 7x+5=54 | | 15-4e=3 | | 3e-3=18 | | 4x=88 | | 6x=88 |